NDVI aplicado na detecção de degradação de pastagens cultivadas - Elaine Lima Fonseca; Marília Locatelli; Eliomar Pereira Silva Filho (Confins)
Grassland degradation is a process according to which occurs loss of productivity, nutritional value and natural recovery capacity. The geoprocessing techniques to identify different levels of degradation through consistent data and repeated measurements. The objective of this research was to use Vegetation Indexes (NDVI) to detect degradation processes of pastures grown in the municipality of Colorado do Oeste – RO. For the study, were used OLI / Landsat satellite images 8 scenes 230/69 and 229/69 for the year 2015, with subsequent verification of a field of pasture conditions. The indexes indicated that 66.69% of the municipality present pastures with some degree of degradation. Of this percentage, 35.19% were classified with moderately (Grassland 3), 24.88% strongly (Grassland 2) and 6.62%, extremely degraded (Grassland 1), and only 33.30% of the pastures in the study area are in adequate production conditions. The methodology used was satisfactory for differentiation of pasture degradation levels.